Cytokinetic failure and asynchronous nuclear division in BHK cells overexpressing a truncated protein-tyrosine-phosphatase. - Cool, D E (1992)
Previous work has shown that a T-cell protein-tyrosine-phosphatase truncated in its carboxyl-terminal domain (delta C11.PTP) has full enzymatic activity but no longer localizes in the particulate fraction of the cell. Two baby hamster kidney (BHK) cell lines overexpressing the truncated protein are markedly multinucleate, a state likely caused by a failure in cytokinesis. Nuclei within syncytial cells overexpressing delta C11.PTP display a remarkable asynchronous entry into mitosis. The effects require tyrosine phosphatase activity because expression of an inactive form of the truncated enzyme yields cells indistinguishable from the parental cell line. Redistribution of the enzyme from the particulate to the soluble fraction is apparently important to these observed effects because cells overexpressing the full-length, wild-type enzyme are morphologically similar to controls. Further, when these cells contain more than one nucleus, their syncytial nuclei undergo mitosis synchronously.